Recovery Procedure for Deeply Discharged LiFePo4 Traction Battery - Matus Danko; Juraj Adamec; Peter Drgona; Michal Frivaldsky (Communications - Scientific letters of the University of Zilina, 2020)
Presented paper deals with possibility of recovery of damaged traction batteries by deep discharge. For the test of proposed charging algorithm, new, unused cell was selected, the deeply discharged condition of which was caused by the self-discharge during the improper storage. The cell had significant damage of package in the central part. For the battery testing, experimental set-up was realized for automated recovering procedure and other tests of cells. For verification of the proposed algorithm, a recovered cell was compared to a reference/new cell by testing the delivered ampere-hours for various discharging current. The final evaluation shows that the proposed algorithm for recovery of the deeply discharged cell can recover up to 70% of the nominal cell capacity.